Warehousing of object oriented petroleum data for knowledge mapping - Nimmagadda, Shastri; Dreher, Heinz; Rudra, Amit (IBIMA, 2005)
Australia produces a-third of world?s natural resources. Enormous amounts of energy and financial resources are expended in order to tap these natural reserves from the earth?s surface. Vast amounts of these resources, however, remain unexplored and under exploited. Data pertaining natural resources, such as mineral and petroleum, are, in general, heterogeneous and complex in nature. Volumes of these types of data are geographically distributed among many companies in Australia and abroad. The existing historical resources data are logically and physically organized using warehousing techniques. Entity relationship (ER) and object oriented (OO) data mapping techniques are used for analyzing the data entities, dimensions and objects. In this paper object oriented data and warehousing of object class data models have been described. Data mining techniques can be employed to explore many more resources hidden, under great depths of the earth?s crust, without additional efforts of exploration and development. Warehoused object oriented resources data can significantly reduce the complexity of the resources data structuring and enhance the data integration and information sharing among various operational units of the resources industry. Large amount of financial inputs can be saved if these technologies are successfully implemented in the resources industry.